La teoría aristotélica de la abstracción y su olvido moderno - Miralbell, Ignacio (Sapientia, 2008)
This study analyzes the aristotelian theory of the abstraction, trying to rescue his original sense from the texts of the author, as well as the contributions of the most relevant medieval aristoteliciens, specially Thomas Aquinas. And then one passes to describe some fundamental milestones of the posterior evolution of the above mentioned theory in the history of the Philosophy, since they are: 1) The contraposition between abstraction and intuition in Duns Escotus and William of Ockham. 2) The intuicionism of Descartes 3) The empirical reintepretation of the abstraction in Locke 4) The absence of the abstraction in Espinoza, Leibniz and Kant, as well as his substitution for the “aufhebung” in Hegel. 5) The peculiar approximation of Husserl to the abstraction from his fenomenological methodology 6) the relation of the theory of the abstraction with the thought of some contemporary authors like Zubiri, Polo and, specially, Heidegger.